BAX-mediated ammonia-driven cell death: a novel prognostic and therapeutic target in clear cell renal cell carcinoma - Xi Zhang; Zijie Yu; Lu Yin; Qiang Li; Shaohua He; Heng Li; Jian Li; Lian Sheng; Hongfei Wu; Hongqi Chen; Xiaoxu Zhu; Yang Lv (Human Genomics)
Abstract Background ccRCC (clear cell renal cell carcinoma) is characterized by metabolic reprogramming and immunosuppression, leading to poor clinical prognosis. In recent years, ammonia-related cell death has attracted increasing attention as a novel mechanism related to tumor progression, but its role in ccRCC has not been clarified. Methods In this study, the Ammonia-related Signature (AS) of ccRCC was constructed by integrating bioinformatics analysis and experimental verification. Multiple independent cohorts including TCGA, PMID 35,440,542 cohort, E-MTAB-1980, and GSE29609 were used to evaluate prognostic accuracy and clinical relevance, and biological functions of key ammonia related genes were explored by cell proliferation, clonal formation, migration, and invasion assays. ScRNA-seq was used to analyze interaction between AS and immune cells in ccRCC. Results The ammonia-related prognostic model demonstrated robust predictive power in multiple datasets. The high AS group of patients with poor prognosis, and the tumor mutation load, immunosuppressive cell infiltration level and immune checkpoint molecular expression were higher. BAX was a key ammonia-related gene closely related to tumor progression, and its knockdown obviously inhibit proliferation, migration and invasion of ccRCC cells. Single-cell analysis confirmed the activation of ammonia-related signaling pathways in the tumor microenvironment, in particular revealing specific interactions between BAX-positive tumor cells and immunosuppressive cell populations. Conclusion The ammonia-related cell death pathway, especially BAX, can be employed as a potential prognostic marker and therapeutic target for ccRCC, providing new ideas for individualized treatment strategies to overcome immunosuppression and improve clinical prognosis.